2016
DOI: 10.1016/j.jcis.2016.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Formation and stabilization of nanoemulsions using biosurfactants: Rhamnolipids

Abstract: Nanoemulsions are used in the food, cosmetics, personal care and pharmaceutical industries to provide desirable optical, textural, stability, and delivery characteristics. In many industrial applications, it is desirable to formulate nanoemulsions using natural ingredients so as to develop label-friendly products. Rhamnolipids are biosurfactants isolated from certain microorganisms using fermentation processes. They are glycolipids that have a polar head consisting of rhamnose units and a non-polar tail consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(132 citation statements)
references
References 45 publications
(58 reference statements)
5
109
1
4
Order By: Relevance
“…S1b). These observations were in accordance with previous studies that indicated a reduction in droplet size with increasing the intensity or duration of disruptive forces generated by the homogenizer (Bai & McClements, 2016;Qian & McClements, 2011). In addition, the particle size distributions at these homogenization conditions were monomodal with an average span value of 1.35 (Fig.…”
Section: Effect Of Extract Concentration and Homogenization Conditionssupporting
confidence: 92%
“…S1b). These observations were in accordance with previous studies that indicated a reduction in droplet size with increasing the intensity or duration of disruptive forces generated by the homogenizer (Bai & McClements, 2016;Qian & McClements, 2011). In addition, the particle size distributions at these homogenization conditions were monomodal with an average span value of 1.35 (Fig.…”
Section: Effect Of Extract Concentration and Homogenization Conditionssupporting
confidence: 92%
“…Also high inhibition zone of synthesized nanoparticles against pathogenic bacteria observed at the same concentration of rhaminolipid and relatively low surfactant concentration was required to produce small droplets of AgNPs. This result were similar with that found by Bai (4). The intensity of the SPR bands increased and shifted to wavelength (500 nm) when the concentration of the rhaminolipid increased from (4 to 6×10 -3 w/v), (Fig.8).…”
Section: Effect Of Rhaminolipid Concentrationsupporting
confidence: 90%
“…Nanoemulsions based on alkyl ether citrates, ethoxylated fatty ethers, or fatty esters of sugars (Inoh et al, 2004) were patented for a use in cosmetic formulations (Simonnet et al, 2002a(Simonnet et al, , 2002b. RL are also described as effective natural surfactant for the formation of O/W nanoemulsions that can be used for personal care formulations (Bai and McClements, 2016). Nanoemulsions can be applied for the delivery of fragrant or for the extension of the fragrance effect in personal care products, while avoiding the use of alcohol in formulations.…”
Section: Personal Care/cosmetics Applicationsmentioning
confidence: 99%